2014
DOI: 10.1002/ijc.29299
|View full text |Cite
|
Sign up to set email alerts
|

Genome wide association study identifies a novel putative mammographic density locus at 1q12‐q21

Abstract: Mammographic density (MD) is an intermediate phenotype for breast cancer. Previous studies have identified genetic variants associated with MD; however, much of the genetic contribution to MD is unexplained. We conducted a two-stage genomewide association analysis among the participants in the "Determinants of Density in Mammographies in Spain" study, together with a replication analysis in women from the Australian MD Twins and Sisters Study. Our discovery set covered a total of 3,351 Caucasian women aged 45 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 42 publications
2
13
0
Order By: Relevance
“…We confirmed associations with SNPs at 13 of 15 previously identified MD loci [10][11][12][13][14] at P < 0.05, nine of which reached genome-wide significance in this study (Supplementary Table 7). Of the two remaining prior loci, rs7289126 at the TMEM184B locus on 22q13.1 had suggestive associations with DA (P = 0.085) and PD (P = 0.083) in the same directions as previously reported 13 .…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…We confirmed associations with SNPs at 13 of 15 previously identified MD loci [10][11][12][13][14] at P < 0.05, nine of which reached genome-wide significance in this study (Supplementary Table 7). Of the two remaining prior loci, rs7289126 at the TMEM184B locus on 22q13.1 had suggestive associations with DA (P = 0.085) and PD (P = 0.083) in the same directions as previously reported 13 .…”
Section: Resultssupporting
confidence: 89%
“…We also report new MD phenotype associations at P < 5 × 10 −8 with SNPs at five prior loci. At the MTMR11 locus on 1q21.1 previously associated with PD 12 , we found that rs11205303 was associated with both DA (P = 6.8 × 10 −20 ) and PD (P = 1.5 × 10 −11 ). At the RALB/INHBB locus on 2q14.2 recently associated with absolute dense volume 10 , we found that rs4849864 was associated with NDA (P = 2.6 × 10 −13 ) and rs17625845 was associated with DA (P = 2.8 × 10 −9 ).…”
Section: Resultsmentioning
confidence: 50%
See 1 more Smart Citation
“…These include: lymphocyte-specific protein 1 ( LSP1 ), which binds f-actin and may be involved with cell migration); RAD51-like 1 ( RAD51L1 ), which is involved in DNA repair and may sense DNA damage; XNF365; and chromosome 12q24 [ 42 44 ]. More recently, the density-associated genes have been extended to include: amphiregulin ( AREG ), an epidermal growth factor (EGF) family member strongly active in breast; ESR1 (estrogen receptor); transmembrane protein 184B ( TMEM184B ), a receptor that can activate MAP kinase; megakaryoblastic leukemia 1 protein ( MKL1 ), which transduces signals from the cytoskeleton to the nucleus, and may trans -activate serum response factor which is downstream of stiffness signals; PR domain containing 6 ( PRDM6 ), a histone methyltransferase that may contribute to proliferation [ 45 ]; early B-cell Factor 1 ( EBF1 ), a transcriptional activator; MIR1972-2 (microRNA), netrin-4, a laminin-related ECM protein; myotubularin-related protein 11 ( MTMR11 ), a pseudophosphatase that can be altered in some breast tumours; and Cezanne, which deubiquitinates EGF receptor and might also be involved in controlling high MD [ 46 , 47 ]. Tab2 , at the 6q25.1 locus, which binds ESR1 and is also involved with interleukin-1 activation of NFκB and MAPK8, is an additional genetic marker for high MD [ 48 ].…”
Section: Introductionmentioning
confidence: 99%
“…MD is highly heritable ( h 2 = 0.60 – 0.65) [ 2 – 5 ] and genetic loci associated with MD can provide insight into the biological mechanisms leading to breast cancer, which may serve as targets for treatment and preventive strategies [ 6 ]. Despite the high heritability, a large proportion of the genetic variation of MD remains unexplained [ 7 9 ]. The Marker of Density (MODE) consortium recently identified nine loci ( AREG , ESR1 , ZNF365 , LSP1/TNNT3 , IGF1 , TMEM184B , SGSM3/MKL1 , PRDM6 , 8p11.23) associated with area-based MD [ 7 , 8 ] as obtained with the semiautomated thresholding method Cumulus [ 10 ].…”
Section: Introductionmentioning
confidence: 99%